2021
DOI: 10.1093/humrep/deab028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the screening results of 24040 potential sperm donors in a human sperm bank in Henan Province, China: a 14-year retrospective cohort study

Abstract: STUDY QUESTION Is there a relation between the characteristics of potential sperm donors and the acceptance rate of these potential donors? SUMMARY ANSWER A relatively higher acceptance rate was observed for potential sperm donors who were aged ≤ 35 years, were married, had children, and who had received higher education, and acceptance rates were also higher during spring and winter than summer and autumn. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…This analysis shows that, during 2018 and 2019, only a small fraction of initial applicants at Cryos in Denmark and the USA were finally accepted as sperm donors and passed all the screening tests such that their frozen samples were certified as being suitable and safe to be released for use. This figure (3.79%) is very similar to that reported by Paul et al (2006) in the Northeast of England (3.63%), but significantly lower that recently reported by Liu et al (2021) in China (23.38%). However, in their numerator, Liu et al (2021) only reported applicants who had previously met the basic requirements, and this probably corresponds closer to the 5996 applicants in our study who passed the initial screening questionnaire ( Fig.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This analysis shows that, during 2018 and 2019, only a small fraction of initial applicants at Cryos in Denmark and the USA were finally accepted as sperm donors and passed all the screening tests such that their frozen samples were certified as being suitable and safe to be released for use. This figure (3.79%) is very similar to that reported by Paul et al (2006) in the Northeast of England (3.63%), but significantly lower that recently reported by Liu et al (2021) in China (23.38%). However, in their numerator, Liu et al (2021) only reported applicants who had previously met the basic requirements, and this probably corresponds closer to the 5996 applicants in our study who passed the initial screening questionnaire ( Fig.…”
Section: Discussionsupporting
confidence: 86%
“…This figure (3.79%) is very similar to that reported by Paul et al (2006) in the Northeast of England (3.63%), but significantly lower that recently reported by Liu et al (2021) in China (23.38%). However, in their numerator, Liu et al (2021) only reported applicants who had previously met the basic requirements, and this probably corresponds closer to the 5996 applicants in our study who passed the initial screening questionnaire ( Fig. 1 ) and who then attended for semen analysis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the 21st century, artificial insemination using a donated sperm sample from a place used to store sperm or the sperm bank has been most widely utilized by persons without a male partner, i.e., single women and women in same-sex partnerships [ 2 ]. Generally speaking, there are age and health background checks that a sperm donor must pass [ 3 ]. In the United States, sperm banks are under the observation of the Food and Drug Administration's Human Cell and Tissue or Cell and Tissue Bank Product regulations.…”
Section: Introductionmentioning
confidence: 99%